Ecology, nature, materialism (Nóema, 2021)
A first part of the essay summarizes the main lines of a recent book by the author: Per un paradigma del corpo: una rifondazione filosofica dell’ecologia, Quodlibet, Macerata, 2019. A paradigm in which body and biology preserve their irreducibility towards culture is maintained, and the “linguistic turn”, which has dominated XXth century’s philosophy, is severely criticized ; accordingly, Merleau-Ponty’s reflection on the concept of nature is considered the most appropriate and up-to-date tool to rethink the ecological question; its consequences in the field of philosophy of technology and of the problem of subject are examined. A second part of the essay, focusing on a meeting between Adorno and Merleau-Ponty which took place in 1961, tries to sketch a materialistic paradigm for ecology, softening Merleau-Ponty’s final proximity to Heidegger.
Keywords: ecology; nature; phenomenology; Merleau-Ponty; philosophy of technology; subject; Heidegger; Adorno; materialism